Prognostic role of serum neutrophil gelatinase-associated lipocalin in cardiac arrest patients: A prospective observational study. Issue 40 (8th October 2021) - Kang, Changshin; In, Yong Nam; Park, Jung Soo; You, Yeonho; Min, Jin Hong; Jeong, Wonjoon; Ahn, Hong Joon; Cho, Yong Chul; Ryu, Seung
Abstract : Abstract: Accurate neurological prognostication is of the utmost importance to avoid futile treatments in patients treated with targeted temperature management (TTM) after out-of-hospital cardiac arrest (OHCA). This study aimed to investigate the prognostic value of serum neutrophil gelatinase-associated lipocalin (NGAL) by comparing with neuron-specific enolase (NSE), which is currently recommended by international guidelines in patients treated with TTM after OHCA. The study included 85 comatose adult patients with OHCA who underwent TTM between May 2018 and December 2020. Serum NGAL and NSE were measured at 24-hour intervals until 72 hours after return of spontaneous circulation (ROSC). The primary outcome was their prognostic performance for poor neurological outcome at 3 months after OHCA. Forty-nine patients (57.6%) had a poor neurological outcome; NGAL levels at all time points measured were significantly higher in these patients than in those with a good outcome ( P  < .01). NGAL showed lower maximal sensitivity (95% confidence interval [CI]) under a false-positive rate of 0% for the primary outcome compared with NSE (18.2% [95% CI 8.2–32.7] vs 66.7% [95% CI 50.5–80.4]). The combination of NGAL with NSE at 48 h showed the highest sensitivity (69.1% [95% CI 52.9–82.4]) and had the highest area under the curve (0.91 [95% CI 0.81–0.96]) for a poor outcome. The prognostic performance of NGAL alone was inadequate at all time points. However, NGAL combined with NSE at 24 and 28 hours after ROSC showed improved sensitivity compared to NGAL alone. NGAL should be considered a supplementary biomarker in combination with NSE for prognostication in patients with OHCA treated with TTM.